The importance of hospital re-accreditation: improving the timeliness of laboratory critical value reporting - Wahyu Febrianto; Menis Rahmawati; I Gede Sastrawan; Tita Hariyanti (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
Background: Patient safety is the main issue in healthcare services nowadays. Delaying to inform the critical value of laboratory results is a significant source of harm for the patient. The aim of this study is to compare the timeliness of laboratory critical value reporting before and after re-accreditation as one of the service quality indicators in Hospital X. Methods: This study was done by using observational cross-sectional in Hospital X on January - February 2020 with total sampling method of critical value reporting to the responsible clinician that originated from Intensive Care Unit (ICU), Verlos Kamer (VK), and inpatient ward (IW) 1-6 from January-December 2019. The timeliness of reporting was counted since the laboratory result was obtained until received by the responsible clinician within £ 30 minutes and categorized as